The Criminal Law Policy Regarding the Death Penalty in Renewing of Indonesian Criminal Law - Yudi Alvisahrin; Eko Soponyono; Umar Ma'ruf (Universitas Islam Sultan Agung, 2022)
This study aims to examine in depth the criminal law policy regarding the death penalty in the renewal of Indonesian criminal law. This research was expected to contribute ideas in the realm of literature in the field of Islamic law as well as input for observers and law enforcers to determine policies related to the death penalty law. To achieve this goal, this research was conducted by observing events or facts deemed relevant to the research, by collecting primary data and secondary data through a juridical-normative approach with qualitative analysis methods. The study with this theme can be concluded that the choice or stipulation of the death penalty as a means to tackle crime is essentially a policy choice. The concept of the draft Criminal Code issues the death penalty from the main criminal system and lists it as a special principal crime or as an exception (special) punishment. These laws are made to maintain the balance of human life in order to create harmony and order.